AGE AND PROVENANCE OF THE ARGUN SERIES SEDIMENTARY ROCKS OF THE ARGUN CONTINENTAL MASSIF: LA-ICP-MS U-Pb AGES OF DETRITAL ZIRCONS - Yu. N. Smirnova; V. B. Khubanov (Геодинамика и тектонофизика)
For the first time there were obtained LA-ICP-MS U-Pb age data on detrital zircons from sediments of the Bystraya and Ernichnaya formations of the Argun series of the northwestern Argun continental massif. The results obtained lead to the following conclusions: (1) the Bystraya series combines heterochronous Low Cambrian carbonate rocks and Upper Proterozoic terrigenous deposits; (2) the age of the youngest group of detrital zircons extracted from sediments of the Ernichnaya formation allows us to restrict the lower age limit to the Ediacaran (556±11 Ma), which does not contradict a standard stratigraphic age; (3) terrigenous materials entering the basin may come from the Argun continental massif. The inferred source areas of clastic materials are the Neo- and Paleoproterozoic magmatic and metamorphic formations, widespread across the Argun massif. Besides, the deposits we studied contain a smaller amount of the Mesoproterozoic zircons. Their provenance still remains unknown since the Argun massif does not include any Mesoproterozoic magmatic rocks with sufficiently accurate geochronological age estimates.